Increasing the chlorine active sites in the micropores of biochar for improved mercury adsorption. (1st October 2018) - Wang, Tao; Wu, Jiawen; Zhang, Yongsheng; Liu, Jun; Sui, Zifeng; Zhang, Huicong; Chen, Wei-Yin; Norris, Pauline; Pan, Wei-Ping
Graphical abstract: Highlights: Mechanism of Hg 0 removal by hydrochloric acid modified biochars was studied. HCl modification increased the Hg 0 adsorption performance of the six biochars. The Cl on the surface of RI and TO significantly decreased after modification. HCl dissolved metals from biochars and increased micropore and mesopore volume. Hg 0 transferred via mesopore and oxidized to Hg 2+ by the Cl in the micropore. Abstract: A series of biochars were prepared from rice(RI), tobacco(TO), corn(CO), wheat(WH), millet(MI), and black bean straw(BB). These biochars were used to study the mechanism of elemental mercury(Hg 0 ) adsorption by hydrochloric acid modified biochars. The biochars were modified by 1 M hydrochloric acid (HCl) and then used in a fixed-bed Hg 0 adsorption experiment. As would be expected, the results indicated that HCl modification increased the Hg 0 adsorption performance of the six biochars. After modification, the Hg 0 adsorption efficiency of tobacco biochar increased from 8.2% to 100.0%, and the average Hg 0 adsorption capacity of the biochars increased by 61 times. The acid modification dissolved the metal compounds in the biochar, reducing the metal content and increasing the average surface area of the biochar. The average surface area of the raw biochars increased from 29.9 to 110.1 m 2 /g after HCl modification. The extra surface area was mostly created in the micropores, leading to a significant increase in the amount of micropores. These micropores effectively adsorbed the Cl atoms, which acted as active sites for Hg 0 . In the adsorption process, Hg 0 diffused into the interior of modified biochars via mesopores, and finally the adsorbed Cl in the micropores reacted with Hg 0 to form HgCl2 .